Research Mapping in the Use of Technology for Fake News Detection: Bibliometric Analysis from 2011 to 2021 - Budi Gunawan; Barito Mulyo Ratmono; Ade Gafar Abdullah; Nada Sadida; Hendra Kaprisma (Indonesian Journal of Science and Technology, 2022)
This study aims to (1) determine research developments, (2) produce research distribution maps based on co-authorship analysis, (3) produce research distribution maps based on citation analysis, (4) produce research distribution maps based on co-citation analysis, (5) produce a research distribution map based on co-occurrence analysis, and (6) find out the state-of-the-art research in the use of technology for fake news detection. This study uses a quantitative method with a descriptive approach in bibliometric analysis from 2011 to 2021. From the research results obtained (1) the development of research publications in the field of the use of technology for fake news detection shows an increase, (2) the interrelationships between countries of authors, organizations affiliated with the authors, and among authors, (3) distribution map of citation analysis based on units of countries, sources, and authors, (4) distribution map of co-citation analysis based on unit cited sources and cited authors, (5) connection of keyword in the use of technology for fake news detection publications is related to literacy skills such as media literacy and information literacy, and (6) several research trends that researchers have widely used in the last 2 years including COVID-19, media literacy, and cyber deception. The research results can be used to determine the development of research o in the use of technology for fake news detection and as a reference for developing further research in the use of technology for fake news detection.